Printing Conflicts in the Middle East (Political Geographic Review) - Manvender Singh (International Journal of Science and Society, 2020)
MiddleEastis aregionwithgeographicalirony. With strong geographicelements and having both physical and non-physical diversepotentials, this region shouldbe politicallypowerful. In fact, Middle East seems like"a hostage held region," where its strategicand potential geographical conditions havetriggered the presenceof foreignforcesinthe region with various political and economical interests fromtimetotime. The presence ofPersian Empire, which later on followed byOttomanTurkeyto the era of France Political Forces of Napoleon, alltried to rulethe region. Likewise, during the First and the Second World War, this area was significantly strategic because itplayed aroleinthe victory of allied countries, asa militarybaseandlogistic track. The region became more significant when oil fields were discovered in the 1940s. This had invited more foreign forces to come particularly the United Statesand the European countries. Conflict of interests of world power in the Middle East continues to put its hegemony until the present days. Variousforeign interestsinthe region,more or less, initiated conflicts in the politics of the region, particularly creating dilemma in the integration of all Arab countries.